New Fe–Cu bimetallic coordination compounds based on ω-ferrocene carboxylic acids and 2-thioimidazol-4-ones: structural, mechanistic and biological studies. Issue 21 (16th September 2021) - Guk, Dmitry A.; Krasnovskaya, Olga O.; Moiseeva, Anna A.; Tafeenko, Victor A.; Ul'yanovskii, Nikolay V.; Kosyakov, Dmitriy S.; Pergushov, Vladimir I.; Ya. Melnikov, Mikhail; Zyk, Nikolay V.; Skvortsov, Dmitry A.; Lopatukhina, Elena V.; Vaneev, Alexander N.; et al.
Abstract : Synthesis, characterization and in vitro cytotoxic investigation of a series of new ferrocene-containing derivatives based on ω-ferrocene carboxylic acids and 2-alkylthioimidazolin-4-ones and their copper complexes have been reported. Abstract : Synthesis, characterization (HRMS, NMR, EPR, UV-Vis spectroscopy, and electrochemistry) and in vitro cytotoxic investigation of a series of new ferrocene-containing derivatives, based on ω-ferrocene carboxylic acids and 2-alkylthioimidazolin-4-ones as well as their copper coordination compounds, have been reported. A series of ferrocene–imidazolone conjugates with different lengths and donor properties of the linker fragments have been synthesized; all the obtained compounds were studied in complexation reactions with copper(i ) and copper(ii ) perchlorates. It is shown that the synthesised conjugates rapidly and efficiently convert coordinating copper ions into the Cu(+1) oxidation state, but a change in the length of the linker in ferrocene–imidazolone ligands fundamentally changes the ratio of products formed as a result of iron oxidation/copper reduction and complexation by various mechanisms. After comparing the data on the qualitative and quantitative composition of the reaction mixtures and the kinetic characteristics of the processes occurring in the mixtures of ferrocene–imidazolones with copper(ii ) perchlorate, a scheme of the ongoing reactions was proposed which may fully explain all the observed processes and products. It has been shown that the obtained bimetallic Cu/Fe coordination compounds are more toxic than cisplatin and induce apoptosis in micromolar concentrations on Hek-293 and MCF-7 cell lines.